Programmable Microfluidics - Thies, Bill; Urbanski, J. P.; Cooper, Mats; Wentzlaff, David; Thorsen, Todd; Amarasinghe, Saman (ASPLOS Wild and Crazy Ideas Session. Boston, MA, 2004)
Recent years have seen tremendous miniaturization of chemical and biological instrumentation that is culminating in the advent of fully integrated “lab-on-a-chip” systems. Such systems out-perform their laboratory counterparts by providing high throughput, reduced reagent consumption, low cost and automatic control. The enabler of these advances is microfluidics: an integrating technology for manipulating fluids at the picoliter scale. Microfluidic chips have demonstrated basic functionality for single applications, but they have been lacking the abstraction layers needed to perform varied and complex experiments on a single platform.